Etiology of Viral hepatitis among acute hepatitis patients at a tertiary care hospital in North India - Mustafa, Zeeshan; Ahmad, Islam; Sami, Hiba; Ali, Syed Ghazanfar; Firoze, Safiya; Raza, Adil; Fatima, Nazish; Khan, Haris M (International Journal of Human and Health Sciences (IJHHS), 2023)
Introduction: Viral hepatitis, a significant public health burden, affects millions of individuals worldwide. HAV, HBV, HCV, and HCV are primary causative agent for viral hepatitis. Large number of outbreaks of HAV and HEV occurs every year. HBV and HCV are primary cause of chronic liver disease. Exploring the etiology and clinic-epidemiological profile of acute viral hepatitis (AVH) becomes crucial for planning the preventive measures to control the diseases. Methods: This study was conducted at VRDL, Department of Microbiology, JNMC, AMU, Aligarh, Uttar Pradesh, India from January 2018 to October 2022. Patients showing symptoms of hepatitis such as jaundice, fever, malaise, headache, nausea, vomiting, anorexia, diarrhoea, and abdominal pain were included in the study. Results: Out of 1798 patients presenting with acute viral disease, 21.02% (378/1798) had HAV, 20.96% (377/1798) had HBV, 9.78% (176/1798) had HCV, and 5.45% (98/1798) had HEV. There were 0.5% (09/1798) samples which were positive for both HBV surface antigen and anti-HCV antibodies and 0.3% (06/1798) samples were positive for both anti-HAV IgM and anti-HEV IgM. With the exception of Hepatitis A, which was more common in children, other Viral hepatitis were more common in adults with a male preponderance. Conclusions: Vaccination, better cleanliness, and appropriate blood screening before blood transfusion are all safety measures that can help to lower the incidence rate of viral hepatitis and stop its spread. Regularly identifying the cause of AVH and keeping track of cases would aid in patient management and help disease control programs make policy decisions. International Journal of Human and Health Sciences Supplementary Issue 02: 2023 Page: S49-S61